Vibration and underwater noise simulation of a river-crossing tunnel based on a 2.5D structural-acoustic finite element method - Zhou, Hualun; Song, Xiaodong; Xiong, Wen; Wu, Hao; Li, Qi; Cai, C.S. (Structures (Oxford), 2024)
To protect the underwater ecosystem and species, the vehicle-induced vibration and underwater radiated noise of river-crossing tunnels need to be calculated efficiently and accurately. For this purpose, this study proposed a 2.5-dimensional (2.5D) structural-acoustic finite element method which combines 2.5D finite element vibration algorithm and 2.5D infinite element acoustic algorithm. The proposed method utilizes the spatial wave number transformation theory and the acoustic transfer vector (ATV) method. Based on a river-crossing tunnel, a 2.5D numerical simulation model was established in this study to analyze the vehicle-induced tunnel-soil vibration as well as the underwater radiated noise during operation. The results showed that the tunnel vibration and the associated radiated noise mainly distributed in the range of 10 to 40 Hz, with two peaks at 15.6 Hz and 31.5 Hz, respectively. The total sound pressure level (SPL) of the predicted noise at each field point reached a maximum value of 126 dB. The 2.5D algorithm proposed in this study achieves higher computational efficiency compared to traditional 3D vibration and noise analysis methods, which can provide theoretical and technical supports for the protection of underwater ecological diversity.